Restrukturisasi Spasial dan Perubahan Pola Pergerakan Pada Kasus Kota Semarang, Bandung dan Jakarta - Kombaitan, B.; Kusumantoro, Iwan P. (Center for Research and Community Services ITB, 1997)
Referring to the experiences of the current urban development, it seems that the process of suburbanization is an inseparable part of urban develo0pment. In addition, suburbanization has a big influence to the shift in the characteristic of the transportation system, especiallu in the fringe area. One important issue in this shift is the changes intrip length. This issue becomes important because in the process of suburbanization, there is a decline in the dependency of the fringe area to the central area. This phenomenon, obviously, can not be percieved in a simple way since the component of the reduction in the trip length will become an important parameter in assesing various policies and practice of urban planning.